The eye of continuous software engineering - Johanßen, Jan Ole; Kleebaum, Anja; Paech, Barbara (Software Engineering und Software Management 2019, 2019)
We summarize the paper Practitioners’ Eye on Continuous Software Engineering: An Interview Study [Jo18], which was presented at the 2018 edition of the International Conference on Software and System Processes (ICSSP) in Gothenburg, Sweden.
Gesehen am 11.12.2019
Keywords: CD-ROM